A 2D CONVERTED-WAVE MODELING STUDIES: COMPARISON OF ISOTROPY AND WEAK ANISOTROPY MODELS UNDER GAS-CLOUD - Bambang Irawan, Jefri
Conventional seismic reflection (P-P) methods have been widely used, among others, for hydrocarbon exploration and imaging subsurface structures. But in certain cases, this method is less than the maximum in imaging the structure and there is ambiguity in the exploration of hydrocarbons. The converted-wave (P-S) seismic method is used to improve the quality of the resulting subsurface image. By using a multicomponent receiver, the P wave is recorded on the vertical component and the S wave is recorded on the horizontal component. The assumption commonly used in seismic data processing is the isotropic medium, but in reality the subsurface medium is an anisotropic medium. Therefore in this study anisotropy model was also made with three different values of the ? (epsilon) parameter to further analyze the effects of this anisotropy. The purpose of this research is to create a 2D subsurface model and to do elastic firing on synthetic models, to compare cross sections produced from isotropy and anisotropy models (PP and PS cross sections), to compare seismic gatherings between isotropic and anisotropy data, and to analyze the magnitude of the resulting amplitude by the anisotropic effect on each model. Data processing is performed on horizontal and vertical components in both models. In horizontal component stacking, depth variant stack is used to get a better cross-sectional image laterally. For the P-P stack section there is more diffraction (bowtie effect) than the P-S stack section. With the same offset, the P-S migration cross section has a better quality than the P-P migration cross section in describing the structure under the gas-cloud. CMP gather anismotropic seismic was corrected using NMO velocity obtained from velocity analysis on an isotropic model and visible hockey stick effect. This effect has an effect on the effective offset obtained in each model and then a subtract trace is performed to examine the difference in amplitude in the isotropy and anisotropy models